Recombinant Saccharomyces cerevisiae strains for improved bioethanol production from starch-based substrates - Myburgh, Marthinus Wessel (Stellenbosch : Stellenbosch University, 2020)
Thesis (MSc)--Stellenbosch University, 2020.